SPK1 is an essential S-phase-specific gene of Saccharomyces cerevisiae that encodes a nuclear serine/threonine/tyrosine kinase. - Zheng, P (1993)
SPK1 was originally discovered in an immunoscreen for tyrosine-protein kinases in Saccharomyces cerevisiae. We have used biochemical and genetic techniques to investigate the function of this gene and its encoded protein. Hybridization of an SPK1 probe to an ordered genomic library showed that SPK1 is adjacent to PEP4 (chromosome XVI L). Sporulation of spk1/+ heterozygotes gave rise to spk1 spores that grew into microcolonies but could not be further propagated. These colonies were greatly enriched for budded cells, especially those with large buds. Similarly, eviction of CEN plasmids bearing SPK1 from cells with a chromosomal SPK1 disruption yielded viable cells with only low frequency. Spk1 protein was identified by immunoprecipitation and immunoblotting. It was associated with protein-Ser, Thr, and Tyr kinase activity in immune complex kinase assays. Spk1 was localized to the nucleus by immunofluorescence. The nucleotide sequence of the SPK1 5' noncoding region revealed that SPK1 contains two MluI cell cycle box elements. These elements confer S-phase-specific transcription to many genes involved in DNA synthesis. Northern (RNA) blotting of synchronized cells verified that the SPK1 transcript is coregulated with other MluI box-regulated genes. The SPK1 upstream region also includes a domain highly homologous to sequences involved in induction of RAD2 and other excision repair genes by agents that induce DNA damage. spk1 strains were hypersensitive to UV irradiation. Taken together, these findings indicate that SPK1 is a dual-specificity (Ser/Thr and Tyr) protein kinase that is essential for viability. The cell cycle-dependent transcription, presence of DNA damage-related sequences, requirement for UV resistance, and nuclear localization of Spk1 all link this gene to a crucial S-phase-specific role, probably as a positive regulator of DNA synthesis.